2004
DOI: 10.1111/j.1365-2036.2004.02164.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: budesonide treatment for collagenous colitis

Abstract: SUMMARYBackground: Collagenous colitis is typified by chronic watery diarrhoea and characteristic histological alterations of the colonic mucosa without endoscopic abnormalities. Budesonide, a corticosteroid with high first-pass metabolism has been examined in collagenous colitis, but studies to date have had small numbers, and relatively low statistical power. Aim: A meta-analysis of existing published trials was undertaken to evaluate the treatment effect of budesonide in collagenous colitis. Methods: All pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…6 Despite this, the effect of current smoking on both the clinical picture at diagnosis and the clinical course of the disease could not be demonstrated in the present study. Of note, clinical remission rate in the present study was near 100%, which is a higher rate than that observed in clinical trials with budesonide, 23 suggesting that most patients included in the present study have mild forms of the disease. Thus, a role of smoking in the clinical course of more severe forms of the disease cannot be ruled out.…”
Section: Discussionmentioning
confidence: 59%
“…6 Despite this, the effect of current smoking on both the clinical picture at diagnosis and the clinical course of the disease could not be demonstrated in the present study. Of note, clinical remission rate in the present study was near 100%, which is a higher rate than that observed in clinical trials with budesonide, 23 suggesting that most patients included in the present study have mild forms of the disease. Thus, a role of smoking in the clinical course of more severe forms of the disease cannot be ruled out.…”
Section: Discussionmentioning
confidence: 59%
“…The lower value allows increased detection of microscopic colitis when FCP levels are raised only slightly. This is a condition of rising prevalence, particularly among the elderly29 30; as symptoms can be relieved with budesonide,31 it is necessary to recognise it which, in turn requires systematic biopsy for diagnostic histopathology. Thus, when colonoscopy appearances are normal in a ‘D-IBS’ patient, the endoscopist when aware of raised FCP would take more biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…It has further been shown that budesonide rapidly achieves clinical remission in the majority of patients, and significantly improves quality of life 6, 13 . Recent literature reviews and meta‐analyses have concluded that budesonide is currently the only intervention for which strong evidence exists for clinical improvement in collagenous colitis 14, 15 . However, the long‐term outcome of patients with collagenous colitis after successful short‐term budesonide therapy is largely unknown.…”
Section: Introductionmentioning
confidence: 99%